Popper theory and risk in engineering - Rojas Lazo, Oswaldo (2013)
This article is outlined the theories of the philosopher Karl Raimund Popper on hypothetical deductive method, problems of induction and demarcation. It is presented concepts of science, technology and engineering and standardization norm. It is developed the theory of risks related to engineering projects